EVALUATE THE IMPACT AND CHALLENGES OF ANTIMICROBIAL RESISTANCE IN PNEUMONIA: A CROSS SECTIONAL STUDY IN TERTIARY CARE HOSPITAL - Sonia khan; Farhana Shams Abbasi; Sahiba Hakro; Muhammad Latif; Fajar Baqer; Partab Puri; Mehjabeen; Khusboo Asif; Syeda Bushra Zaidi; Muhammad Talha; Misha Fatima (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The rise of antimicrobial resistance (AMR) poses a significant threat to treating infections like pneumonia. In Pakistan, limited access to culture and sensitivity tests often leads to unchecked infections. Therapy failure and frequent antibiotic switching signal drug resistance and AMR.Objectives:The study underscores the need for optimized antibiotic use, improved diagnostics, and strategies to combat AMR. Effective solutions will help mitigate resistance, enhance treatment outcomes, and reduce the burden of infections. MethodologyThe study analyzed 50 pediatric pneumonia cases to assess antibiotic prescription patterns, hospital stay duration, antibiotic consumption, switching, and patient discharge outcomes. This evaluation aimed to understand treatment approaches, identify potential areas for improvement, and optimize patient care. Results: The study results showed that pneumonia is more common in children (1-5 years); n=20 (40%), followed by neonates (0-12 months); n= 16 (32%), respectively. Monotherapy was used upon initial admission of patients, while combination therapy and antibiotic switching occurred when patients didn't respond. Non-responsiveness prolonged hospital stays, suggesting drug-resistant bacteria.The average hospital stay was 6.5 days with monotherapy and 3.5 days with combination therapy. Cefoperazone (28%), meropenem (26%), and vancomycin/linezolid (20%) were the most prescribed antibiotics. Meropenem+linezolid (n=9) and meropenem+vancomycin (n=7) were common combinations. Conclusion: The study reveals a concerning trend of drug-resistant bacterial strains causing pneumonia in pediatric patients, signaling a potential silent pandemic of antimicrobial resistance (AMR). This emerging threat requires careful monitoring and reporting to mitigate its consequences.